Endocrine Adjuvant Therapy might Impair Cardiac Autonomic Regulation in Breast Cancer Survivors - Lucini, Daniela; Malacarne, Mara; Oggionni, Gianluigi; Gatzmeier, Wolfgang; Santoro, Armando; Pagani, Massimo (Cardiology and Cardiovascular Medicine, 2019)
Introduction: Cardiovascular diseases and mortality represent a major issue in breast cancer survivors (BCS). Unhealthy lifestyle and some side effects of long term adjuvant therapy may contribute to increase cardiovascular risk. Autonomic Nervous System (ANS) impairment may contribute to initial cardiovascular alteration and early detection of its malfunction in clinical settings could help foster cardiovascular health in these patients. Methods: This observational study involved 229 outpatient subjects subdivided into three groups: 1) BCS under long term Adjuvant Endocrine Therapy (AET), 2) BCS not on AET, 3) matched healthy controls. Autoregressive spectral analysis of cardiovascular variabilities furnished markers of ANS control, considering simple time and frequency domain classifiers (such as RR variance), and meta-classifiers (such as the index alpha, combining RR and arterial pressure oscillatory information, or ANSI, a percent ranked multivariate unitary index of Autonomic control). Patients’ history, medical examination, blood tests and a lifestyle questionnaire, focusing on exercise, nutrition, and stress, were also employed. Results: Amplitude indices of ANS regulation (in particular RR variance) appeared progressively (p<0.001) reduced from Controls to Patients not receiving (AET-) and to those receiving (AET+) endocrine therapy; similar changes were observed for meta-classifiers (particularly ANSI: 65.2 ± 21.7; 56.9 ± 27.7; 43.1 ± 26.2, p<0.001)). Conclusion: Endocrine therapy is associated with impaired autonomic regulation. Autoregressive spectral analysis of heart rate variability may be an affordable and convenient tool to furnish, in a clinical setting, early markers of cardiovascular dysregulation, which may possibly contribute to an overall increased cardiovascular risk.